Northrop Frye on Literature and Society, 1936-89 - Frye, Northrop (Book collections on Project MUSE., 2002)
Drawn from previously unpublished essays, talks, reviews and papers, this volume of Northrop Frye's collected works spans some fifty years of his long writing career.